Posterior corneal topographic changes after partial flap during laser in situ keratomileusis. Issue 2 (1st February 2003) - Sharma, N; Rani, A; Balasubramanya, R; Vajpayee, R B; Pandey, R M
Abstract : Aim: To study the posterior corneal topographic changes in eyes with partial flaps during laser assisted in situ keratomileusis (LASIK). Methods: Case records of 16 patients, who had partial flap in one eye during LASIK (group 1) and uncomplicated surgery in the other eye (group 2), were studied. Following occurrence of partial flap intraoperatively, laser ablation was abandoned in all the eyes. A 160/180 μm flap was attempted during the initial procedure using the Hansatome microkeratome (Bausch & Lomb Surgicals, Munich, Germany). LASIK surgery in all cases was performed using a 180 μm plate, at the mean interval of 4.16 (SD 1.5) months following the initial procedure. None of the eyes had intraoperative complication during LASIK. Relative posterior corneal surface elevation above the best fit sphere (BFS) before the initial procedure, before, and after LASIK were compared using the Orbscan slit scanning corneal topography/pachymetry system. Results: Posterior corneal elevation was comparable in the two groups, both preoperatively (group 1; 16.4 (4.8) μm, group 2; 16.1 (4.8) μm) and after final surgery (group 1; 57.2 (15.6) μm, group 2; 54.3 (13.1) μm). In group 1 after occurrence of partial flap, the posterior corneal elevation was 16.9 (4.4) μm, and this increase was not significant statistically (p=0.4). On multiple linear regression analysis, residual bed thickness (p<0.001) was independently the significant determinant of final posterior corneal elevation in both groups. Conclusion: The inadvertent occurrence of partial flap during LASIK procedure does not contribute to the increase in posterior corneal elevation.